Factors that influence complementarity and competition between medicinal plants and medicines of biomedical origin in an urban context - Oliveira, Bianca Melo; Santoro, Flavia Rosa; Ferreira Júnior, Washington Soares (Ethnobiology and Conservation, 2024)
Intermedicality is understood as a space of interaction between different medical systems in a given location, which can result in competition or complementarity. In urban environments, intermedicality is common between the biomedical system and other systems. In these scenarios, it is important to understand the therapeutic strategies used by people to treat illnesses, to identify whether the treatment systems adopted lead to competition or complementarity. Among the various factors that can influence these strategies are: people's current and past contact with the rural environment, visits to biomedical environments and socioeconomic factors (income, education and age). This study investigated the therapeutic strategies linked to the complementary or competitive use of medicinal plants and biomedical drugs in an urban environment. The study was carried out in the urban perimeter of the city of Araripina-PE, using an online form addressed to its residents. The form was made up of questions about the therapeutic strategies employed by people, with dissemination through social media and face-to-face visits to institutions and public places. The survey involved 298 residents. Generalized Linear Models, binomial family, were used to assess the effect of the predictor variables on the response variables. As a result, the best-fitting models showed that Complementarity was positively influenced by income and negatively by rural origin, and Competition was positively influenced by rural origin. This study suggests important mechanisms that may be regulating the use of medicinal plants and medicines of biomedical origin exclusively through competition or combined use of these resources in urban contexts.